The glucocorticoid receptor in osteoprogenitors regulates bone mass and marrow fat. Issue 1 (October 2019) - Pierce, Jessica L; Ding, Ke-Hong; Xu, Jianrui; Sharma, Anuj K; Yu, Kanglun; del Mazo Arbona, Natalia; Rodríguez-Santos, Zuleika; Bernard, Paul J; Bollag, Wendy B; Johnson, Maribeth H; Hamrick, Mark W; Begun, Dana L; et al.
Abstract : Excess fat within bone marrow is associated with lower bone density. Metabolic stressors such as chronic caloric restriction (CR) can exacerbate marrow adiposity, and increased glucocorticoid signaling and adrenergic signaling are implicated in this phenotype. The current study tested the role of glucocorticoid signaling in CR-induced stress by conditionally deleting the glucocorticoid receptor ( Nr3c1 ; hereafter abbreviated as GR) in bone marrow osteoprogenitors (Osx1-Cre) of mice subjected to CR and ad libitum diets. Conditional knockout of the GR (GR-CKO) reduced cortical and trabecular bone mass as compared to WT mice under both ad libitum feeding and CR conditions. No interaction was detected between genotype and diet, suggesting that the GR is not required for CR-induced skeletal changes. The lower bone mass in GR-CKO mice, and the further decrease in bone by CR, resulted from suppressed bone formation. Interestingly, treatment with the β-adrenergic receptor antagonist propranolol mildly but selectively improved metrics of cortical bone mass in GR-CKO mice during CR, suggesting interaction between adrenergic and glucocorticoid signaling pathways that affects cortical bone. GR-CKO mice dramatically increased marrow fat under both ad libitum and CR-fed conditions, and surprisingly propranolol treatment was unable to rescue CR-induced marrow fat in either WT or GR-CKO mice. Additionally, serum corticosterone levels were selectively elevated in GR-CKO mice with CR, suggesting the possibility of bone–hypothalamus–pituitary–adrenal crosstalk during metabolic stress. This work highlights the complexities of glucocorticoid and β-adrenergic signaling in stress-induced changes in bone mass, and the importance of GR function in suppressing marrow adipogenesis while maintaining healthy bone mass.